Computer Technology and Students’ Social Cultural Values in Selected Secondary Schools in Kabale District. - Ninsiima, Comfort (Kabale University, 2024)
This study adopts a descriptive research design, utilizing both quantitative and qualitative methods to investigate how technology affects cultural beliefs and social behaviors among secondary school students in selected schools in Kabale District. The research involves 20 students, 5 administrators, and 5 IT teachers, ensuring diverse perspectives within the educational context. Structured surveys gather quantitative data on technology usage frequency, perceived effects (positive and negative), and access to technology at home. Additionally, administrators and IT teachers undergo in-depth interviews to provide qualitative insights into technology integration and its impact on students' socio-cultural values. The study's main objectives are to analyze both the positive and negative impacts of technology on students' socio-cultural values and suggest strategies for integrating technology while preserving cultural heritage and ethical principles. By combining surveys and interviews, the research aims to explore the intricate relationship between technology usage and cultural beliefs, illuminating how digital tools influence social behaviors and cultural identity among secondary students. Through a mixed-methods approach, this study aims to offer a comprehensive understanding of technology's multifaceted impact on socio-cultural values in secondary education. The findings have potential implications for educational policies, curriculum design, and teaching methodologies, aiming to achieve a balanced integration of technology that respects cultural diversity and ethical considerations.